2009
DOI: 10.1166/jnn.2009.1344
|View full text |Cite
|
Sign up to set email alerts
|

Si<SUB>3</SUB>N<SUB>4</SUB>–TiN Nanocomposite by Nitration of TiSi<SUB>2</SUB> and Consolidation by Hot Pressing and Spark Plasma Sintering

Abstract: Homogeneous nanostructured Si3N4-TiN composite powder was obtained by nitration of a TiSi2 powder precursor in a nitrogen flow. Mechanoactivation of titanium disilicide increases the nitration rate and reduces the temperature of formation of the Si3N4 and TiN. The properties of hot pressing (HP) and spark plasma sintering (SPS) of the nanostructured Si3N4-TiN composite with Y2O3 and Al2O3 additives have been studied. In the case of the HP-prepared composite the processing conditions are sufficient to form a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The SPS was performed using a “Dr. Sinter” apparatus (Sumitomo, Japan) . Initially, a pressure of 20 MPa was applied to ensure sufficient electric contact between the powder tablet and the graphite die.…”
Section: Methodsmentioning
confidence: 99%
“…The SPS was performed using a “Dr. Sinter” apparatus (Sumitomo, Japan) . Initially, a pressure of 20 MPa was applied to ensure sufficient electric contact between the powder tablet and the graphite die.…”
Section: Methodsmentioning
confidence: 99%
“…This property of SPS is of undoubted significance in the case of manufacture of bulk nanostructured parts, for which the control of grain growth is one of the major problems (H. Borodianska et al, 2008;O. Vasylkiv et al, 2008;H. Borodianska et al, 2009).…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
“…Among the reactive consolidation techniques, spark plasma sintering (SPS) is gaining in popularity [23][24][25][26]. In a recent report on hightemperature reaction-driven spark plasma sintering (RSPS) of TiB 2 -TaC ceramics, Demirskyi et al [22] reported the formation of a hard (28 GPa) tantalum titanium carboboride phase during consolidation that involved the dissolution of titanium diboride into a newly formed (Ta,Ti)C carbide.…”
Section: Introductionmentioning
confidence: 99%